Ketamine in chronic pain: A Delphi survey. (8th February 2022) - Voute, Marion; Riant, Thibault; Amodéo, Jean‐Marie; André, Gilbert; Barmaki, Mario; Collard, Olivier; Colomb, Caroline; Créac'h, Christelle; Deleens, Rodrigue; Delorme, Claire; de Montgazon, Géraldine; Dixneuf, Véronique; et al.
Abstract: Background: There is no recommendation in Europe for the use of ketamine in patients with chronic pain. The heterogeneity of practice highlights the need to seek the advice of experts in order to establish a national consensus. This Delphi survey aimed to reach a national consensus on the use of ketamine in chronic pain in Pain clinics. Methods: A collaborative four‐round internet‐based questionnaire was used. It was created after literature search on ketamine administration in chronic pain and included about 96 items. It discussed utility and advantages, adverse events and deleterious aspects, methods of administration, concomitant treatments and assessment of results. Results: Twenty‐eight experts completed all rounds of the survey with a total of 81.3% items reaching a consensual answer. Neuropathic pain represents the first indication to use ketamine, followed, with a good to moderate utility, by other situations (fibromyalgia, complex regional pain syndrome, central neuropathic pain, peripheral neuropathic pain, nociceptive pain, sensitization, opioid withdrawal, palliative care, depression). Experts agreed on the rare occurrence of adverse events. Concerning routes of administration, intravenous infusion with doses of 0.5–0.9 mg/kg/d for 4 days of treatment is preferred. Place of care is hospital, as in‐ or out‐patient, with a quarterly administration of ketamine. Finally, ketamine effectiveness is assessed 1 month after infusion, and experts encourage combination with non‐pharmacological treatment. Conclusions: This Delphi survey established a consensus of pain specialists on the use of ketamine in refractory chronic pain, thus providing a basis for future comparative trials. Significance: This Delphi survey in chronic pain reached agreement on four main aspects: (1) Priority to treat neuropathic pain with evaluation of effectiveness at 1 month; (2) No deleterious effects in the majority of listed diseases/situations with the absence or <3% of suggested adverse events; (3) 0.5–0.9 mg/kg/d IV infusion; (4) Combination with non‐pharmacological treatment.